INDONESIA'S EFFORTS TO ACHIEVE A UNIVERSAL WELFARE STATE THROUGH THE FAMILY HOPE PROGRAM (PKH) IN BANDUNG REGENCY, WEST JAVA INDONESIA - Karina Puji Fauziah; Ida Widianingsih; Dedi Sukarno (DIA: Jurnal Administrasi Publik, 2026)
This study aims to analyze the impact of the implementation of the Family Hope Program (PKH) in West Java, focusing on factors that influence its effectiveness and efficiency. Using a qualitative approach, this study explores various dimensions that play a role in the success of the program, such as organizational capacity, coordination between institutions, communication, and the role of the community in the implementation process. This study combines primary data obtained through in-depth interviews with key informants, such as Village Heads, PKH Coordinators, and Beneficiary Families (KPM), as well as field observations, with secondary data collected from related documents and previous studies. The results of the study indicate that various challenges in the implementation of PKH in West Java, such as inaccuracy in determining the target of beneficiaries, the length of time required for registration, and difficulties in graduating KPM, are greatly influenced by the dimensions of Organization, Interpretation and Application. In addition, the lack of coordination between institutions and limited resource capacity at the local level have slowed down the program implementation process. This study provides insight into the need for reform in the management and evaluation of PKH so that this program can be more effective in achieving its goals of empowering poor communities and improving the welfare of beneficiary families in West Java.